SANKSI SEBAGAI PEMODERASI PENGARUH MANAJEMEN LABA, LIKUIDITAS DAN LEVERAGE PADA KETEPATAN WAKTU PELAPORAN KEUANGAN - Sinta Maha Dewi, A. A. Sagung; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
Timeliness is the factors presenting an update because it encourages investors to invest in the company so interested parties can take the relevant decisions. This study aim to determine sanctions as a moderating influence earnings management, liquidity and leverage on the timeliness of financial reporting. The population are all mining companies listed on the Indonesia Stock Exchange 2013-2015 period. Determination the sample using purposive sampling method obtained 78 samples. The hypothesis was tested using logistic regression analysis to test Moderated Regression Analysis (MRA). Based on results show earnings management, liquidity and leverage has no effect on the timeliness of financial reporting and sanctions are not able to moderate the effect of earnings management on the timeliness of financial reporting. Sanctions are not able to moderate the effect of liquidity on the timeliness of financial reporting but sanctions able to moderate the effect of leverage on the timeliness of financial reporting.
Keywords: Timeliness, Earnings Management, Liquidity, Leverage, Sanctions